Dynamic System Modeling of Renewable Energy Diversification at ITS Surabaya as a Sustainable University Management Effort - Arishinta, Ayasophia; Suryani, Erma (Institut Teknologi Sepuluh Nopember, 2020)
Diversification is an effort to diversify various energy sources through reducing the use of fossil energy sources and substituting them with other energy sources including RE in order to optimize energy supply. Meanwhile, energy conservation is a systematic, planned and integrated effort to conserve existing energy resources and increase the efficiency of their use. Energy has a very significant role in human life in all sectors. Where energy demand in the commercial sector such as offices and services is still largely dominated by electricity around 60% -70%. Where the management is still largely managed by the State Electricity Company (PLN). The electricity consumption of the ITS Surabaya campus in 2019 around 9,586,857.72 kWh / year is still supported by PLN with a total expenditure of more than 9 billion. Considering the Indonesian government's program on the Target of Diversification of RUEN at least 23% in 2025 and 31% in 2050 and one of the 2030 Agenda for Sustainable Development Goals (SDGs) globally namely clean and affordable energy, the ITS Surabaya management effort is to achieve diversification of energy sources 50% renewable as stated in the 2015-2020 RENSTRA Target. The effort to diversify this renewable energy is by building a 16 KWP On Grid Solar Power Plant in the Research Center Building, which has produced around 26,290.92 kWh / year during the 2019 period.